Modeling and Optimization of the Process of Hopped Beer Wort with Topinambur Additives (Eurasian Journal of Engineering and Technology, 2022)
In this work, we have studied the color of young beer with the addition of Jerusalem artichoke additives, in which it increases, and more than 10% replacement of malt with Jerusalem artichoke can inhibit the fermentation process. It was determined that the color within the standard is maintained with the addition of up to 10% Jerusalem artichoke additives, and this dosage is considered the maximum possible in the production of light beers.